Association of Rate of Functional Recovery With Therapy Time and Content Among Adults With Acquired Brain Injuries in Inpatient Rehabilitation - Alison M. Cogan, PhD, OTR/L; Pamela Roberts, PhD, OTR/L, SCFES, FAOTA, CPHQ, FNAP, FACRM; Trudy Mallinson, PhD, OTR/L, FAOTA, FACRM (Archives of Rehabilitation Research and Clinical Translation)
Objective: To examine associations among the time and content of rehabilitation treatment with self-care and mobility functional gain rate for adults with acquired brain injury. Design: Retrospective cohort study using electronic health record and administrative billing data. Setting: Inpatient rehabilitation unit at a large, academic medical center. Participants: Adults with primary diagnosis of stroke, traumatic brain injury, or nontraumatic brain injury admitted to the inpatient rehabilitation unit between 2012 and 2017 (N=799). Interventions: Not applicable. Main Outcome Measures: Gain rate in self-care and mobility function, using the Functional Independence Measure. Hierarchical regression models were used to identify the contributions of baseline characteristics, units, and content of occupational therapy, physical therapy, and speech-language pathology treatment to functional gain rates. Results: Median length of rehabilitation stay was 10 days (interquartile range, 8-13d). Patients received an mean of 10.62 units of therapy (SD, 2.05) daily. For self-care care gain rate, the best-fitting model accounted for 32% of the variance. Occupational therapy activities of daily living units were positively associated with gain rate. For mobility gain rate, the best-fitting model accounted for 37% of the variance. Higher amounts of physical therapy bed mobility training were inversely associated with mobility gain rate. Conclusions: More activities of daily living in occupational therapy is associated with faster improvement on self-care function for adults with acquired brain injury, whereas more bed mobility in physical therapy was associated with slower improvement. A potential challenge with value-based payments is the alignment between clinically appropriate therapy activities and the metrics by which patient improvement are evaluated. There is a risk that therapists and facilities will prioritize activities that drive improvement on metrics and deemphasize other patient-centered goals.